Integrating Edpuzzle into Islamic Education: A Quantitative Analysis of Student Engagement and Learning Outcomes at SDIT Nurul Ilmi Jambi - M Syukri Ismail; Ulfa Adilla; Selvia Nelis (Ar-Fachruddin: Pendidikan Agama Islam, 2025)
Research Objective – This study aims to examine the impact of integrating Edpuzzle, an interactive video learning tool, on student engagement and learning outcomes in Islamic Education (PAI) at SDIT Nurul Ilmi Jambi. Methodology – A quantitative quasi-experimental design was employed with non-equivalent control groups. Two fifth-grade classes participated: one using Edpuzzle (experimental) and the other traditional instruction (control). Data were collected through pre-tests, post-tests, and engagement questionnaires. Statistical analyses included descriptive statistics and independent t-tests. Findings – The results indicated that students in the Edpuzzle group outperformed the control group in both learning outcomes (M = 84.3 vs. 75.8, p < 0.001) and engagement (total engagement score M = 4.31 vs. 3.76, p < 0.001). Significant improvements were observed across behavioral, emotional, and cognitive dimensions of engagement. Research Implications/Limitations – The study supports the integration of interactive video tools in PAI to enhance engagement and academic achievement. However, the findings are limited to one school with a small sample size, and future research should explore broader contexts and diverse student populations. Originality/Value – This study provides empirical evidence of the effectiveness of Edpuzzle in Islamic education settings, offering practical insights for educators aiming to modernize pedagogy through technology without compromising religious content. It contributes to the discourse on digital transformation in Islamic education in Indonesia.